Maldives : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2008)
The Seventh National Development Plan of the Maldives envisages sustainable development with economic growth, social equity, environment protection, and good governance. The report assesses the policies and strategies needed to achieve the goals as well as the agencies responsible to implement the policies. It also summarizes the principles, vision, and goals of the National Development Plan (NDP) and assesses the economic, spatial, social development, and governing factors of the plan. It discusses the priorities, responsibilities, and accountabilities for development, and assessed that monitoring and evaluation is necessary for higher performance and greater accountability.